Injury prevention in professional soccer players: can re-warmup training be organized in the post-warmup and half-time during a soccer game in a short time? - D`Onofrio, R.; Laterza, F.; Sannicandro, I.; Masucci, M.; Bovenzi, A.; Manzi, V. (The Journal of Sports Medicine and Physical Fitness, 2024)
INTRODUCTION: Passive time, during the post-warmup and half-time, decreases athletes` performance and increases injury risk factors in the active phases of the soccer match. Objective. This narrative review aims to research and synthesize existing evidence to identify brief re-warmup strategies that may find applicability in the post-warmup and half-time of a soccer match. EVIDENCE ACQUISITION: The analysis was conducted on PubMed, Web of Science, PEDro, SPORTDiscus and Google Scholar. Due to the lack of evidence, no temporal time was established, preferring most up-to-date articles. The data were synthesized in relation to the objectives, following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. EVIDENCE SYNTHESIS: Our research yielded a total of 753 studies, 463 related to re-warmup, 136 articles on re-warmup in soccer, and 154 articles on re-warmup during half-time. Of these, 26 met the inclusion objectives and were included in this research. Our findings confirm that a re-warmup can mitigate the decremental effect of static rest on performance. From the studies considered, we have identified a work that emphasizes how a 1-minute warmup of high-intensity exercise at speed corresponding to 90% of VO2max can prevent decreases related to passive time, in sprint performance and muscle strength, as well as improve muscle temperature. These results could apply to both post-warmup and half-time scenarios of a soccer match. CONCLUSIONS: From this narrative review, it has been possible to highlight a one-minute high-intensity re-warmup that improved sprint performance, increased core temperature, and enhanced muscle activation, not leading to additional physiological or psychological fatigue.